Newborn mice vaccination with BCG.HIVA²²² + MVA.HIVA enhances HIV-1-specific immune responses: influence of age and immunization routes. - Saubi, N; Im, E; Fernández-Lloris, R; Gil, O; Cardona, P; Gatell, J; Hanke, T; Joseph, J (2011)
We have evaluated the influence of age and immunization routes for induction of HIV-1- and M. tuberculosis-specific immune responses after neonatal (7 days old) and adult (7 weeks old) BALB/c mice immunization with BCG.HIVA(222) prime and MVA.HIVA boost. The specific HIV-1 cellular immune responses were analyzed in spleen cells. The body weight of the newborn mice was weekly recorded. The frequencies of HIV-specific CD8(+) T cells producing IFN-γ were higher in adult mice vaccinated intradermally and lower in adult and newborn mice vaccinated subcutaneously. In all cases the IFN-γ production was significantly higher when mice were primed with BCG.HIVA(222) compared with BCGwt. When the HIV-specific CTL activity was assessed, the frequencies of specific killing were higher in newborn mice than in adults. The prime-boost vaccination regimen which includes BCG.HIVA(222) and MVA.HIVA was safe when inoculated to newborn mice. The administration of BCG.HIVA(222) to newborn mice is safe and immunogenic and increased the HIV-specific responses induced by MVA.HIVA vaccine. It might be a good model for infant HIV and Tuberculosis bivalent vaccine.